Arab Mediterranean youth: political and religious participation - Kenneth Roberts; Siyka Kovacheva; Stanimir Kabaivanov (Revista CIDOB d'Afers Internacionals, 2018)
Using data from the SAHWA Youth Survey 2016 (2017), this paper presents a study of the degree and types of political and religious participation – as well as the links that connect one to the other – among the youth of five Arab Mediterranean countries (Morocco, Algeria, Tunisia, Egypt and Lebanon). In politics, four types of participation are distinguished: official, everyday, community and protest. Between 5% and 17% of those surveyed could be considered hyperactivists, in that they participate in three or four of these types; in around a third, there was no participation at all. On the other hand, the majority of the young people considered themselves to be highly religious and, in three of the countries, a third attended the mosque at least three times a week. But the levels of religiosity did not influence political participation, as even the majority of the highly religious supported separating politics from religion.